ANALISIS PERBEDAAN RETURN SAHAM, TRADING VOLUME ACTIVITY DAN BID-ASK SPREAD SEBELUM DAN SESUDAH STOCK SPLIT - Widiatmoko, Arif; Paramita, V. Santi (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
The purpose of this research is to know stock return, trading volume activity and ¬bid-ask spread before and after stock split at company listed in Indonesia Stock Exchange. This study was conducted on all companies listed in Indonesia Stock Exchange 2010-2014 period with the number of research samples of 30 companies through purposive sampling technique. Data collection method used is non-participant technique with data analysis technique Paired Samples T-Test. Based on the result found that there is no difference between stock return, trading volume activity and ¬bid-ask spread before and after stock split.